LINKS TO RUSSIAN LITERATURE IN GOHAR MARKOSIAN- KASPER’S NOVEL "PENELOPE" - AVETISYAN, VENERA (Bulletin of Yerevan University H: Russian Philology, 2019)
Markosyan-Kasper’s novel “Penelope” is rich with references to Russian, foreign and antique literature. The author considers in this article references to Russian literature. The role of the references is determined in the new context, where one day a woman from Yerevan named Penelope turns into an Odysseus, compared with “Ulisses” by James Joyce.
Keywords: Gohar Markosian-Kasper,